Respiratory Syncytial Virus Lower Respiratory Tract Infections in Premature Infants and Infants with Bronchopulmonary Dysplasia - D. Yu. Ovsyannikov; D. N. Degtyarev; I. V. Krsheminskaya; L. M. Makarova; M. A. Ovsyannikova; O. V. Cilinskaya; I. E. Turina; L. V. Malutina; T. A. Pugacheva; S. V. Cherkasova; N. I. Petruk; A. M. Bolibok; et al. (Детские инфекции (Москва))
The article is devoted to the study of features of lower respiratory tract infection associated with respiratory syncytial virus. 40 cases of RSV-bronchiolitis in preterm children under year with/without bronchopulmonary dysplasia were analyzed. It was established that disease in those groups of patients had severe course because of the respiratory failure, which dominates in clinical pictures as symptoms of bronchial obstruction and apnea. Treatment of severe RSV-infection often demand admission to intensive care unit, supplemental oxygen and/or mechanical ventilation.